MicroRNA-188 aggravates contrast-induced apoptosis by targeting SRSF7 in novel isotonic contrast-induced acute kidney injury rat models and renal tubular epithelial cells - Liu, Bowen; Chai, Yunfei; Guo, Wei; Lin, Kaiyan; Chen, Shiqun; Liu, Jin; Sun, Guoli; Chen, Guangzhong; Song, Feier; He, Yibo; Liang, Yan; Guo, Zhaodong; et al. (Annals of translational medicine, 2019)
Contrast media (CM) is widely used in cardiac catheterization; however, it may cause contrast-induced acute kidney injury (CI-AKI) which severely increases mortality. MicroRNA (miRNA) has been found to participate in the process of acute kidney injury (AKI), and this discovery has great potential for diagnosis and treatment. However, the role of miRNA in CI-AKI is still unclear. This study aimed to investigate the regulatory effect miRNAs exert in CI-AKI. We established a novel, representative, isotonic CI-AKI model by using CM iodixanol, a CM which is commonly used in clinic. Next-generation sequencing and reverse transcription polymerase chain reaction (RT-qPCR) were performed to determine the expression of miRNA-188 in CI-AKI. Western blot analysis of the apoptosis regulator protein and TUNEL assay were ordered to evaluate apoptosis. Bioinformatics and double luciferin reporter gene assay were performed to predict and to confirm the interaction between microRNA-188 and SRSF7. The novel isotonic CI-AKI rat model we established exhibited typical characteristics of CI-AKI in serum creatinine, cystatin C, HE staining, and under electron microscope observation. Sequencing and RT-qPCR demonstrated that miRNA-188 was significantly up-regulated both in CI-AKI rat and HK-2 cell models while overexpression of miRNA-188 significantly aggravated apoptosis in CI-AKI cell models. SRSF7 was identified as a direct target gene of miRNA-188, and dual luciferase reporter assay determined the direct interaction between SRSF7 and miRNA-188. In addition, SRSF7 silencing reduced the cell viability rate of the CI-AKI cell model. The present study's findings indicate that miRNA-188 aggravated contrast-induced apoptosis by regulating SRSF7, which may serve as a potential drug target for CI-AKI intervention.